Maintenance of Dry Organic Fertilizer Mixer Machine of Tobacco Agriculture - Susilawati Susilawati; Masri Bin Ardin; Annisa Oktaviani (Universitas Sultan Ageng Tirtayasa, 2021)
The purpose of this study was to make a preventive maintenance plan for the dry organic fertilizer mixing machine for tobacco farming with the Inspection, Small repair, Medium repair, Overhaul which is called ISMO method. The steps of the study carried out were data collection by observation and literature studies, then component identification, maintenance schedules, maintenance procedure plans and expert validation. The results of the study are the preventive maintenance schedule for the mixer machine consisting of a monthly schedule and an annual schedule using the ISMO method. The total time required for inspection maintenance activities is 240 minutes, small repair is 210 minutes, and medium repair is 20 minutes. Based on the validation results, the maintenance schedule has been feasible to be applied to a dry organic fertilizer mixer machine for tobacco farming and total maintenance time used along a year are inspection 240 minutes, small repair 214 minutes and medium repair as 20 minutes.